(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the symptoms of anxiety, depression, and perceived stress in patients in the immediate preoperative period of the first elective surgery for colorectal cancer, and investigate the association/correlation of these symptoms with sociodemographic and clinical variables. Methodology: an observational, analytical, cross-sectional study with 89 patients in a public university hospital in the State of São Paulo, Brazil. The Hospital Anxiety and Depression Scale (HADS) was used to assess symptoms of anxiety and depression, and the Brazilian Perceived Stress Scale (BPSS-10) for perceived stress, and a validated instrument to obtain sociodemographic and clinical data. Results: There was a slight predominance of women (50.6%); mean age of 61.8 years and 7.3 years of study; 78.7% declared themselves white; 60.7% with a partner, and 76.4% were unemployed. The mean score for anxiety was 7.4 (median=8.0, SD=4.1), for depression was 4.2 (median=3.0, SD=3.8) and for perceived stress was 20.0 (median=19, SD=7.6). Women and patients younger than 60 years old had more symptoms of anxiety and perceived stress; men and the elderly showed more symptoms of depression. There was a strong correlation between symptoms of anxiety, depression, and perceived stress, and a moderate correlation between perceived stress and time to start treatment, all of which were statistically significant. Conclusion: Although patients had different levels of anxiety, depression, and perceived stress in the immediate preoperative period, there was no statistically significant association/correlation between these symptoms and other sociodemographic and clinical variables.